A PHYSIOTHERAPY MANAGEMENT IN CASES OF LUMBAL NUCLEUS PULPOSUS (HNP) HERNIA USING MICROWAVE DIATHERMY (MWD) AND MC MODALITY KENZIE EXERCISE - Anadhiyah, Zulfa; Yudistra, Efraldo; Shiddiqi, Toumi (JURNAL PROFESIONAL FISIOTERAPI, 2024)
Background: Pulpous Nucleus Hernia (HNP) is a condition where protraction occurs in the intervertebral disc due to injury or excessive mechanical load. HNP is a condition where the nucleus pulposus in the annulus fibrosus comes out or protrudes, puts compression on the nerves, and causes radicular pain, motor weakness, numbness, or tingling. Mc.Kenzie Exercise and the use of Microwave Diarrhea (MWD) modalities to overcome this problem. Microwave Diathermy (MWD) reduces pain caused by damaged tissue or abnormal tissue by stimulating the nociceptors, while giving McKenzie exercise aims to improve normal posture in the vetebra, reducing pressure on the intervertebral disc and vetebra ligaments. Method: The research method is a case study to determine the management of physiotherapy in cases of Lumbar Hernia Nucleus Pulposus (Hnp) Using Microwave Diathermy (Mwd) and Mc. Kenzie Exercise Results: Management of the physiotherapy process during 9 meetings using Microwave Diathermy (MWD) and Mc. Kenzie Exercise in lumbar HNP patients has been carried out according to standards with surgery, resulting in increased joint range of motion and increased functional activity. Conclusion: MWD modality, Mc. Kenzie exercise in HNP patients can increase the range of joint movement and functional activity in patients Keywords: Microwave diathermy (MWD), Mc. Kenzie exercise, Hernia Nuckleus Pulposus (HNP)